Berardinelli-Seip congenital lipodystrophy 2/SEIPIN determines brown adipose tissue maintenance and thermogenic programing - Hongyi Zhou; Cheng Xu; Hakjoo Lee; Yisang Yoon; Weiqin Chen (Elsevier, 2020)
Objective: Understanding the mechanisms that control brown adipose tissue (BAT) mass and functionality is crucial for our understanding of how the disruption of energy homeostasis leads to obesity. Bernerdinali Seip Congenital Lipodystrophy (BSCL) type 2 (BSCL2, a.k.a. SEIPIN), a lipodystrophy-associated protein, has been shown to not be required for brown adipogenesis, but it has been shown to be essential for perinatal BAT development. However, its role in mature BAT maintenance and thermogenic programing remains poorly understood. Methods: We subjected Bscl2f/f and Bscl2UCP1-BKO (BKO) mice with a brown adipose-specific loss of BSCL2 through UCP1 promoter-driven Cre to environmental, pharmacological and diet interventions to challenge BAT functionality and reprogramming. We carried out physiological, molecular and transcriptomic analyses of BAT. Results: The deletion of BSCL2 in mature brown adipocytes increased sympathetic nervous system-independent cAMP/protein kinase A (PKA) signaling in BAT. Such activation reduced BAT triglyceride content and mass and was sufficient to reduce plasma triglyceride, but not enough to combat thermoneutral and high fat diet-induced obesity. Surprisingly, BKO mice displayed an impaired response to acute and chronic cold challenges despite cAMP/PKA activation. When subjected to chronic cold exposure or the administration of a β3-adrenergic agonist, CL 316,243, BKO mice failed to induce BAT recruitment and underwent dramatic brown adipocyte loss. Transcriptomic analysis revealed pathological BAT remodeling with inflammation and fibrosis, which was further exacerbated by a chronic thermogenic challenge in BKO mice. Mechanistically, we found abnormal mitochondrial shapes and function in BAT of BKO mice housed at 21 °C; as well as mitochondrial DNA depletion and necroptotic-mediated brown adipocyte death after chronic thermogenic insult. Conclusion: BSCL2-mediated lipid catabolism within BAT is crucial for mature brown adipocyte function and survival both during times of activation and quiescence. BSCL2 is an important regulator of mature brown adipocyte mitochondrial metabolism, necroptosis and thus adaptive thermogenesis.